Opazovanje in spremljanje glasbenega razvoja - priložnost, da prisluhnemo otroku kot kompetentnemu glasbeniku - Borota, Bogdana (Revija za elementarno izobraževanje, 2012)
In the preschool period, adults have an important role of planning and assessing childrens development and learning. It is the very connection between the two adult activities that increases the quality of educational work. The practice of assessing childrens musical development and learning has not been the subject of systematic research yet; therefore, the paper theoretically discusses and explains the key elements of assessment with the help of examples on early musical development in preschool children. The applicability of theory is reflected in the observation checklist items, which should be tested and developed in practice. Furthermore, the paper indicates (1) the difference in the variety of documentation material on observation and assessment and (2) the connection between assessment and further curriculum planning in the field of music. The aim of the research presented henceforth is to identify the situation in the field of observation and assessment of musical development with special emphasis on determining the frequency of observations and the techniques used to record them. The results of the research, conducted among 810 experts from Slovenian preschools, reveal that preschool teachers consider themselves important factors in stimulating childrens musical development and as such, keep records of musical development of preschool children. However, they do not record it systematically or often enough, so that we could determine the efficiency of assessment in relation to planning the process-development model of learning and teaching music.
Keywords: predšolska vzgoja; predšolski otroci; otroški vrtci; glasbena vzgoja; glasbeni razvoj; music; glasba